Preferences for the far future / Marek Steinke and Stefan Trautmann - Marek Steinke; Stefan T. Trautmann (University of Heidelberg, Department of Economics, 2021)
Both research and anecdotal evidence suggest that people care about long-run environmental outcomes, but often fail to act sustainably, endangering environmental stability. For a large population sample, we show that people substantially value the environment intrinsically, i.e., even after their own and their kin's lifespan. Willingness-to-pay for very long-run environmental benefits not experienced by the respondent is similar to that of short-run benefits, experienced by the respondent. However, adding a cooperation problem through uncertainty about other people's preferences significantly decreases participants' willingness-to-pay for both time frames, with respondents being pessimistic about others' willingness to contribute.
urn:nbn:de:bsz:16-heidok-306376
Keywords: 330